Different mechanisms mediating cybervictimization and internalizing/externalizing problems: The moderating role of emotion regulation strategies. (July 2023) - Wang, Zhenhai; Tao, Zhiyuan; Lan, Yilin; Chen, Yanrong; Xie, Qiheng; Li, Qinghan; Lu, Canjie; Zhang, Wei
Abstract: Being victimized online and through social media is a prevailing phenomenon among adolescents, and has been shown to be associated with later internalizing and externalizing problems. However, there is insufficient understanding of how the experience of cybervictimization is associated with these problems and when these associations are strongest. Guided by general strain theory, we proposed that cybervictimization is associated with internalizing and externalizing problems through different mechanisms, and that emotion regulation strategies moderate these processes. Questionnaire data were collected from 810 high school students in southern China (54.3% girls, mean age = 16.8, SD = 0.79). As hypothesized, path analysis results showed that the positive association between cybervictimization and internalizing problems was mediated by psychological insecurity, whereas the positive association between cybervictimization and externalizing problems was mediated by moral disengagement. In addition, adolescents' emotion regulation strategies moderated these mediation processes. Cognitive reappraisal buffered the effect of psychological insecurity on internalizing problems but aggravated the effect of cybervictimization on moral disengagement. Expressive suppression buffered the effect of moral disengagement on externalizing problems. Our results provide a novel perspective for understanding the negative impacts of cybervictimization on adolescents, and have practical implications for interventions to reduce these impacts. Highlights: Cybervictimization is associated with adolescents' internalizing and externalizing problems. Moral disengagement and psychological insecurity mediated these two pathways, respectively. Cognitive reappraisal and expressive suppression play a moderating role in the above relationships. The results have practical implications for developing targeted prevention and intervention programson cybervictimization.